Sistema solar fotovoltaico conectado à rede elétrica operando como gerador de potência ativa e compensador de potência reativa - Albuquerque, Fabio Lima de (2012)
The principal agent guiding this work was the development by computer simulations of the control of a voltage sourced inverter (VSI) to replace the current sourced inverter (CSI) commonly employed in photovoltaic (PV) systems, using the standard PWM (pulse width modulation). This control aims to adjust the power angle according to the energy provided by the PV system and therefore to increase/decrease the active power supplied to the grid. It also changes the magnitude of the voltage vector at the inverter terminals to meet the need of supplying /absorbing reactive power. Later, in order to verify the practical application of the technique used in this work, it is examined through computer simulations and field measurements, the influence of PV generation in the load curve of a residential area, a public organization and a commercial area in Palmas city, state of Tocantins. It was evaluated the characteristics of the load curve in relation to active, reactive and apparent power, and power factor, at point of access to the distribution grid, under various percentages of PV system penetrations. Another aspect analyzed, for these same areas, is the inclusion of photovoltaic systems with reactive power compensation through inverter control, which provides active power and compensates reactive power for the distribution grid. With respect to the residential area, it was also considered the use of solar water heaters to replace electric showers in order to reduce the active power consumed during the peak hours. It is shown that the developed control presented a satisfactory performance since the active power supplied by the PV system to the grid increases with irradiation rise. With regards to reactive power, it is increased by inverter action as soon as active power is reduced due to irradiation decline.